Генезис та сутність понять «ризик», «ризик-менеджмент» та «операційні ризики» - Сторожук, Н. В. (Ways to Improve Construction Efficiency, 2012)
The article analyzes the history of the origin of the concepts of "risk", "risk management" and "operations management." The essence of the studied concepts and offered their vision for their determination.